VARIOUS ASPECTS OF ANTHROPOGENIC MATERIAL FLOWS IN THE CZECH REPUBLIC: PRESENTATION OF THE PROJECT - Kovanda, Jan; Hak, Tomas (European Scientific Journal, ESJ, 2013)
This article presents a project supported by Grant Agency of the Czech Republic and carried out at the Charles University in Prague, Environment Center. The project is being carried out in 2012- 2014 and its overall goal is to evaluate various aspects of anthropogenic material flows in the Czech Republic such as the trends of overall environmental pressures related to material flows, the shifts of these pressures among countries due to international trade, efficiency of material use, recycling and product specificity of material-based pressures. The project applies approaches of ecological economics including economy-wide material flow accounting and hybrid input-output life cycle assessment method. These approaches are considered well established and suitable tools for monitoring and evaluation of human-induced material flows and related environmental pressures. The project has four objectives: 1) Extension of time series of economy-wide material flow indicators for the Czech Republic and assessment of their trends; 2) Compiling a material flow indicator related to recycling; 3) Extension of material flow indicators by water accounts; 4) Identification of product groups within the Czech economy, which are related to largest environmental pressures. The article further shows some first results of the above project, which include the decrease in environmental pressure related to use of materials in 2009 and 2010, increasing rate in recycling and increasing pressure exerted on the environment due to surface water abstraction.